2010
DOI: 10.2147/opth.s10804
|View full text |Cite
|
Sign up to set email alerts
|

Influence of container structures and content solutions on dispensing time of ophthalmic solutions

Abstract: PurposeTo investigate the influence of container structures and content solutions on the time of dispensing from eye dropper bottles.MethodsEye dropper bottle models, solution models (filtrate water/surfactant solution) and a dispensing time measuring apparatus were prepared to measure the dispensing time.ResultsWith filtrate water and pressure thrust load of 0.3 MPa, the dispensing time significantly increased from 1.1 ± 0.5 seconds to 4.6 ± 1.1 seconds depending on the decrease of inner aperture diameters fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Davis et al summarized rates of eyedrop instillation failure as follows: between 18.2 and 80% of patients contaminate their eyedrop bottle by touching their eye or face, 11.3-60.6% instill more than one drop, and 6.8-37.3% miss the eye when attempting to instill a drop [7]. Many factors are reported to be related to instillation failure: older age, insufficient instruction on the eyedrop instillation technique, female sex, arthritis, inadequate posterior bending of the head, much more severe visual-field defects, lack of positive reinforcement to take eyedrops, lower educational level, low self-efficacy, shape and hardness of eyedropper bottles, drug viscosity, and being seen at a clinic rather than a private practice [7][8][9][10][11][12]. However, previous results were not consistent.…”
Section: Introductionmentioning
confidence: 99%
“…Davis et al summarized rates of eyedrop instillation failure as follows: between 18.2 and 80% of patients contaminate their eyedrop bottle by touching their eye or face, 11.3-60.6% instill more than one drop, and 6.8-37.3% miss the eye when attempting to instill a drop [7]. Many factors are reported to be related to instillation failure: older age, insufficient instruction on the eyedrop instillation technique, female sex, arthritis, inadequate posterior bending of the head, much more severe visual-field defects, lack of positive reinforcement to take eyedrops, lower educational level, low self-efficacy, shape and hardness of eyedropper bottles, drug viscosity, and being seen at a clinic rather than a private practice [7][8][9][10][11][12]. However, previous results were not consistent.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the structure of eye drop bottles has been improved in recent years, so that patients can instill one drop into their eyes accurately [1,2]. Therefore, the efficacy of topical IOP-lowering medications likely depends on the accuracy of self-instillation.…”
Section: Introductionmentioning
confidence: 99%
“…Eyedropper bottles with center-dimpled shapes showed greater force differences between the first and second drops, which means that this shape is useful for avoiding multidrop instillation. Yoshikawa et al reported that the dispensing time was mostly influenced by the diameter of the inner aperture of bottles [7]. When we decide on the design of eyedropper bottles, we have to pay attention to these points.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that glaucoma patients use on average two types of eye drops [6]. Some reports show different squeezing forces among eyedroppers [711], which may affect proper usage.…”
Section: Introductionmentioning
confidence: 99%